2016
DOI: 10.1159/000445630
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Promotes Proliferation and Migration of Follicular Outer Root Sheath Cells via Wnt/β-Catenin Signaling

Abstract: Background/Aims: To investigate the effect and molecular mechanism of EGF on the growth and migration of hair follicle outer root sheath (ORS) cells. Methods: Intact anagen hair follicles were isolated from mink skin and cultured with EGF in vitro to measure ORS daily growth. Meanwhile, purified primary ORS cells were treated or transfected with EGF, and their proliferation and migration were assessed by MTT assay and transwell assay, respectively. The signaling pathway downstream of EGF was characterized by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 28 publications
(27 reference statements)
2
46
0
1
Order By: Relevance
“…As shown in Figure 6, AdWnt10b transfection up-regulated the protein expression of β-catenin in the DPCs (P < 0.0001). Treatment with XAV-939, which is a specific inhibitor of Wnt/β-catenin signaling that promotes the degradation of β-catenin to block the Wnt/β-catenin signaling pathway [21], could reduce the β-catenin protein expression in DPCs (P < 0.0001).…”
Section: Wnt10b Activates the Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…As shown in Figure 6, AdWnt10b transfection up-regulated the protein expression of β-catenin in the DPCs (P < 0.0001). Treatment with XAV-939, which is a specific inhibitor of Wnt/β-catenin signaling that promotes the degradation of β-catenin to block the Wnt/β-catenin signaling pathway [21], could reduce the β-catenin protein expression in DPCs (P < 0.0001).…”
Section: Wnt10b Activates the Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…Investigation of EGF in the hair cycle generated conflicting data, since P.J. Miettinen et al, H. Zhang et al assumed EGF importance in hair follicle development and hair growth (Miettinen, 1995;Zhang et al, 2016a;Zhang et al, 2016b). Kashiwagi et al, Richardson et al showed dose and time dependent EGF effect on hair growth, using an animal model (Kashiwagi et al, 1997;Richardson, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Эти факторы роста оказывают свое действие на волосяной фолликул аутокринно или паракринно. Стоит отметить, что большинство исследований по изучению влияния факторов роста на цикл волосяного фолликула проводились с отдельными факторами роста, в то время как в организме они работают в синергии друг с другом [33][34][35][36]. Таким образом, актуально проведение исследований различных сочетаний факторов роста по установлению их способности участвовать в развитии выпадения волос.…”
Section: Discussionunclassified